A Tree Structure Based Key Generation Technique for Data Security Enhancement - Manikandan, G.; Rajendiran, P.; Harish, V.; Kumar, Nooka Sai (Research Journal of Pharmacy and Technology, 2017)
The key generated from the trees are stored in an array in a different combination of the three keys. Since 3 keys are obtained from three trees we get 3! (i.e.) 6 combinations of keys generated and stored in that array as shown in table 1. First the data is decrypted by Blowfish algorithm and the obtained text from Blowfish is decrypted by DES algorithm to get the original plain text. First the data is decrypted by the RC6 algorithm then by AES algorithm to get the original plain text. Key combinations are generated and stored in an array. * From the array one key is chosen by Key index=length (AVL key + Binary Tree key + BST key) % 6 * If the key size is < 128 then 56-bit encryption algorithm is used to encrypt the plain text (here DES and Blowfish algorithm).